Shulhu Concept Analysis for Appropriate Product Dispute Resolution in Sharia Financing - Lubis, Rahmat Husein; Aprilia, Vera (JIOSE: Journal of Indonesian Sharia Economics, 2023)
This study focuses on how the pattern of sharia economic dispute resolution that occurs in the right sharia financing products BTPN Syariah MMS Siabu. Researchers want to examine how the pattern of dispute resolution can be resolved. The researcher wants to examine the factors that cause the dispute and analyze it with the shulh concept in the Compilation of Sharia Economic Law at the research locus. This research is qualitative research where the type of empirical legal research. The data analysis technique in this research, namely by collecting data, then directing the data, then it will be presented in the form of a narrative conclusion. The conclusion from this study is that the factors that cause this dispute occur because when providing data on prospective customers there is no transparency, dishonesty of information, then problems with economic conditions, and the circumstances of the customer's family are appropriate for the sharia financing. Then for the pattern that is the right product for Islamic financing in a non-litigation way, namely with a warning system, withdrawing deposit funds, account officers going to the floor, and follow-up analysis. Whereas the method of settlement pattern for BTPN Syariah MMS Siabu's sharia financing products is by the principle of shulh murabaha in the Compliance for Sharia Economic Law, which gives a message of peace by the principles of Islamic teachings if there is a dispute it must be amicable.